Optimalisasi Kompetensi Guru melalui Workshop Digital storytelling Berbasis Canva untuk Mendukung Pembelajaran Abad ke-21 di Sukabumi: Optimizing Teacher Competence through a Canva-Based Digital Storytelling Workshop to Support 21st-Century Learning in Sukabumi - Ati Susilawati; Dyah Lyesmaya; Ayi Abdurahman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
The digital transformation in education demands that teachers develop innovative and engaging learning media. One medium relevant to this demand is digital storytelling, which integrates narrative, visuals, audio, and digital technology into meaningful learning experiences. However, initial observations indicate that most teachers in the Cibadak and Cicurug Districts of Sukabumi Regency still use conventional learning methods and lack adequate skills in developing digital storytelling. This community service activity aims to improve teachers' competency in designing and producing digital storytelling using AI and the Canva platform. The implementation method consists of preparation, needs identification, material delivery, demonstration, guided practice, presentation of work, and evaluation. Teachers from various educational levels actively participated in the workshop. The results showed an increase in participants' understanding of digital storytelling, their ability to create storyboards, write narrative scripts, use Canva features, and produce simple digital storytelling products ready for use in learning. Furthermore, participants responded positively to the workshop and stated that the material provided was relevant to the learning needs in schools. The digital storytelling workshop proved an effective strategy for improving teachers' digital literacy while supporting the implementation of creative, student-centered learning. In the future, ongoing mentoring is needed to ensure teachers can consistently implement digital storytelling in the classroom.